2016
DOI: 10.1103/physrevphyseducres.12.020140
|View full text |Cite
|
Sign up to set email alerts
|

Connecting self-efficacy and views about the nature of science in undergraduate research experiences

Abstract: Undergraduate research can support students' more central participation in physics. We analyze markers of two coupled shifts in participation: changes in students' views about the nature of science coupled to shifts in self-efficacy toward physics research. Students in the study worked with faculty and graduate student mentors on research projects while also participating in a seminar where they learned about research and reflected on their experiences. In classroom discussions and in clinical interviews, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
0
23
0
4
Order By: Relevance
“…Nevertheless, perceiving one's own contributions to research as meaningful is similar to feeling a sense of personal achievement when working on a project, which is a component of project ownership [3,5,7]. Inspired by Quan and Elby [11] and Hu et al [9], we speculate that students' sense of project ownership may be coupled to their view of experimentation as a process that they can meaningfully participate in and learn from.…”
Section: Connections Between Views About Experimental Physics and mentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, perceiving one's own contributions to research as meaningful is similar to feeling a sense of personal achievement when working on a project, which is a component of project ownership [3,5,7]. Inspired by Quan and Elby [11] and Hu et al [9], we speculate that students' sense of project ownership may be coupled to their view of experimentation as a process that they can meaningfully participate in and learn from.…”
Section: Connections Between Views About Experimental Physics and mentioning
confidence: 83%
“…It is plausible that, when working on a project, students' views about experimental physics can promote their sense of project ownership. For example, Quan and Elby [11] explored the coupling of students' views about the nature of science and their self-efficacy toward physics research. They demonstrated that, for some undergraduate students, "shifts in seeing research as a place where novices can participate led students to see themselves as able to make a meaningful research contribution."…”
Section: Connections Between Views About Experimental Physics and mentioning
confidence: 99%
“…In addition, in the context of open-ended multiweek projects in a lab course focused on contemporary experimental physics, Eblen-Zayas [33] showed that metacognitive activities and in-class discussions that were "intended to normalize the feelings that students had when progress was slow or frustration grew" had positive impacts on measures of students' enjoyment and confidence with respect to experimentation. Together, these studies [28][29][30][31][32][33] suggest that multiweek projects can support students' development as competent and confident physicists.…”
Section: B Multiweek Projects In Physics Lab Coursesmentioning
confidence: 99%
“…In a study of students enrolled in an advanced lab course, Irving and Sayre [31] argued that student collaboration on "long and difficult physics experiments" facilitated students' introduction to the "authentic expectations, practices, content knowledge, and discourses" of practicing physicists (p. 14). Quan and Elby [32] explored noncognitive aspects of semester-long research projects. They showed that some students experienced coupled shifts in both their views about the nature of science and their beliefs about their ability to contribute to research.…”
Section: B Multiweek Projects In Physics Lab Coursesmentioning
confidence: 99%
“…Students involved in OI-based learning experiences have the authentic opportunity to perform researchlike activities as real scientists. Definitely, this contributes to achieving a robust awareness of the process of scientific inquiry and a deeper view of the nature of science [40][41][42][43]. As a matter of fact, engineering students, in particular, are too often focused on mechanically solving standard problems with the only aim of passing the exam, encountering many difficulties when facing nonstandard problems about everyday phenomena.…”
Section: Theoretical Background and Research Rationalementioning
confidence: 99%